A study of effect of aminoglycoside therapy on auditory brainstem evoked responses in preterm and term neonates - Kumar, Mukesh; Parakh, Manish; Dabi, D. R.; Gupta, B. D. (International Journal of Contemporary Pediatrics, 2020)
Background: Aminoglycosides are widely used drugs in neonates with associated ototoxic side effects, that can be diagnosed with auditory brainstem evoked responses, which is the recommended screening technique in neonatal intensive care unit infants. This study was conducted to evaluate the effect of aminoglycoside therapy on auditory brainstem evoked responses in term and preterm neonates. Methods: A cross-sectional case control study. Two groups of 26 term and 22 preterm neonates who received aminoglycosides, with no other known risk factors for ototoxicity, were compared with suitable matched control group of 10 neonates in each. ABER was done after at least 5 days of aminoglycoside therapy and results were compared to suitable matched controls. Results: Mean latency of wave I in term neonates at 90 dB and 60 dB and mean interwave latencies of I-V waves in preterm neonates at 30 dB was higher in study group and statistically significant. No statistically significant difference in any of ABER parameters was observed in any group, at all other intensities. Conclusions: Wave I latency was prolonged in study group of term neonates at two intensities which indicates effect of aminoglycoside therapy on distal portion of acoustic nerve. But as there were no such findings at other intensities in term study group and in preterm study group and moreover no other ABER abnormalities were observed, it was concluded that the aminoglycoside therapy has low potential for ototoxicity. Authors support the ABER screening for early detection of hearing abnormalities, and recommend study on larger group of neonates and meta-analysis for final conclusion for evidence-based recommendations to use aminoglycosides in neonates, in view of audiometric and neurological abnormalities.